Heat transfer enhancement in parabolic trough receivers using inserts: A review. (December 2021) - Allam, M.; Tawfik, M.; Bekheit, M.; El-Negiry, E.
Highlights: Using inserts enhances the thermal performance of parabolic trough concentrators. Using inserts increases pressure drop through parabolic trough receivers. Twisted tape inserts are widely studied based on bibliometric statistical analysis. Fins inserts achieved an optimum thermal and hydraulic performance. Nanofluids showed better performance than conventional HTFs. Abstract: Utilizing solar energy in power generation or industrial thermal processes became necessary to overcome the environmental impacts of using fossil fuels besides their depletion. Concentrated solar power (CSP) provides an efficient solution for the thermal application of solar energy. A parabolic trough concentrator (PTC) is one of the most widely used CSP technologies to work at temperatures up to 400 °C. Enhancing the thermal performance of PTC requires focusing on increasing the thermal efficiency of its thermal receiver as the most critical element in a PTC system. The inserts enhance the thermal performance of PTCs. This paper reviews studies on various inserts used for heat transfer augmentation in PTCs receivers, outlining the key findings of the literature either with conventional or nanofluids HTFs. It also offers a framework to research trends in PTC thermal enhancing approaches via inserts by providing a statistical bibliometric analysis of the literature, including the share of research per insert type. Finally, this framework addresses the thermo-physical properties and combinations of various nanoparticles and base-fluids of nanofluids HTFs, revealing research prospects for nanoparticle–base fluid combinations.